Specialized representations of value in orbital and ventrolateral prefrontal cortex: desirability versus availability of outcomes - Rudebeck, Peter H. (Neuron, 2017)
Advantageous foraging choices benefit from an estimation of two aspects of a resource’s value: its current desirability and availability. Both orbitofrontal (OFC) and ventrolateral (VLPFC) prefrontal areas contribute to updating these valuations, but their precise roles remain unclear. To explore their specializations, we trained macaque monkeys on two tasks: one required updating representations of a predicted outcome’s desirability, as adjusted by selective satiation; the other required updating representations of an outcome’s availability, as indexed by its probability. We evaluated performance on both tasks in three groups of monkeys: unoperated controls and those with selective, fiber-sparing lesions of either OFC or VLPFC. Representations that depend on VLPFC—but not OFC—play a necessary role in choices based on outcome availability; in contrast, representations that depend on OFC—but not VLPFC—play a necessary role in choices based on outcome desirability.